Short, Mid, and Long-Term Melatonin Exposure Alleviates the Effects of Abamectin on the Antioxidant Defense Mechanism in the Midgut of Spodoptera litura (Insecta: Lepidoptera) - Subala, Subramanian Panchu Ravindra Rajan; Shivakumar, Muthugounder Subramanian (Free Radicals and Antioxidants)
Introduction: Melatonin (N-acetyl-5-methoxytryptamine), a serotonin derivate, is a powerful antioxidant due to its capacity to stimulate the innate immune response in plants and animals. However, in invertebrates, few studies have been conducted to verify the protective effect of melatonin in the antioxidant defense system. Objectives: This study aimed to evaluate melatonin antioxidant role in short-term (24 hr), intermediate (72 hr), and long-term (144 hr) effects against abamectin, the family of avermectins exposure in the midgut of S. litura. Materials and Methods: Melatonin affects ROS generation, nitrite content, protein carbonyl content, TBARS levels, antioxidant enzymes (SOD, GST, CAT, and GPx), ascorbic acid levels, and AChE levels were studied. Results: Results showed that abamectin exposure substantially increases nitrite, TBARS, and ascorbic acid levels (p<0.001). In contrast, long-term melatonin exposure (144 hr) declined ROS, carbonyl content, SOD, GPx, AChE, and ascorbic acid levels (p<0.05). Short-term melatonin exposure (24 hr) was also observed to be effective by significantly reducing (p<0.05) ROS, GST, and Gpx levels in abamectin-exposed animals. Similarly, long-term melatonin exposure (144 hr) showed small DNA fragments similar to control and expression of 100 and 75kDa proteins because of its protective mechanism in insects. Similarly, luzindole, a melatonin antagonist, has small DNA fragments because of its blocking actions on the melatonin receptors in insects. Conclusion: The present study shows that melatonin reduces free radical generation and has protective effects on pesticide-exposed insects, especially in long-term exposure to animals. This effect of indoleamine may be a possible strategy to prevent the damage caused due to abamectin exposure in animals.
Keywords: Abamectin; Antioxidant enzymes; Hormone; Lepidoptera; Midgut; Oxidative stress; Pesticide